Contact models and numerical methods for metal forming processes - Chabrand, Patrick (European Journal of Computational Mechanics, 2005)
The aim of the present study was first, on the macroscopic scale, to investigate the use of dynamic friction models in the analysis of tribological devices and secondly, on the microscopic scale, to analyse the shear off of two surface asperities. The effects of the macroscopic model which was found to fit a Stribeck curve will be discussed. The results will be compared with those obtained in a study performed with a constant friction coefficient. The microscopic analysis is the first step in a study of friction in terms of the plastic deformation of surface asperities. From the numerical point of view, methods used to account for the frictional contact problems in both contexts, those involving the contact occurring between rigid and deformable bodies and between two deformable bodies will be presented in detail.